Job Satisfaction Unveiled: A Deep Dive into Employee Experience in Private Educational Institutions - Raja, Farrukh Latif; Syed, Sumaiya; Hyder, Shahbaz (Pakistan Journal of Humanities and Social Sciences, 2025)
This study examines the fundamental understanding of job satisfaction from the perspective of employee experience to unveil their level of job satisfaction in private educational institutes of Ghotki City, located in Sindh, Pakistan. It is carried out to expand the limited empirical research on the issue. Data from 189 employees working in private educational institutions in Ghotki district representing different schools were collected using a survey method. This study suggests that employee job satisfaction is required to meet the dynamic and ever-increasing problems of maintaining organizational productivity by keeping their staff engaged and motivated at the workplace, satisfied employees are more productive. However, the high level of neutrality and dissatisfaction may indicate areas where employee satisfaction can be improved. The study is limited by its sample size and design, and the satisfaction level of other staff related to different cities is not studied in this study. This study opens the way to understanding practical consequences that help to demonstrate the need for adopting a more self-sacrificing leadership style to increase job satisfaction. Pakistan leaders in the examined region must be aware of the benefits of this method for job satisfaction, which can eventually assist in engaging workers and improving their performance.